Fruit Preservation Novel and Conventional Technologies - Rosenthal, Amauri; Deliza, Rosires; Welti-Chanes, Jorge; Barbosa-Cánovas, Gustavo V. (Food Engineering Series,, 2018)
Fruits and fruit based products are, in most cases, associated with very good sensory characteristics, health, well-being, perishability, relatively easy to mix with food products of diverse origin, amenable to be processed by conventional and novel technologies. Given the multiplicity of aspects whenever fruit preservation is considered, the editors took the challenge of covering in a thorough, comprehensive manner most aspects dealing with this topic. To accomplish these goals, the editors invited well known colleagues with expertise in specific disciplines associated with fruit preservation to contribute chapters to this book. Eighteen chapters were assembled in a sequence that would facilitate, like building blocks, to have at the same time, a birds-eye view and an in-depth coverage of traditional and novel technologies to preserve fruits. Even though processing took center stage in this book, ample space was dedicated to other relevant and timely topics on fruit preservation such as safety, consumer perception, sensory and health aspects. FEATURES: Traditional and Novel Technologies to Process Fruits Microwaves Ohmic Heating UV-C light Irradiation High Pressure Pulsed Electric Fields Ultrasound Vacuum Impregnation Membranes Ozone Hurdle Technology Topics Associated with Fruit Preservation Safety Nutrition and Health Consumer Perception Sensory Minimal Processing Packaging Unit Operations for Fruit Processing Cooling and Freezing Dehydration Frying.